Ambiances et civilité - Anthony Pecqueux (Ambiances)
This paper is a critical review of the recent French translation of Erving Goffman’s Behavior in Public Places, in order to discuss a few connections between interaction’s microsociology and ambiances studies. For this purpose, it relates first the book’s main contributions, especially from the attention-sensitive’s point of view and its situated organisation. Secondly, the paper follows the tracks proposed by Goffman towards urban ambiances, understood as the affective tone through which individuals interact and that they can alter with their interactions and presences. Finally, the paper rests on The Wire and Treme TV series in order to illustrate and continue the discussion about ambiances and civility.